Examining the relationship between arterial stiffness and swim-training volume in elite aquatic athletes - Cheung, C. P.; Coates, A. M.; Currie, K. D.; King, T. J.; Mountjoy, M. L.; Burr, J. F. (European Journal of Applied Physiology, 2021)
Purpose: Factors such as prone body position, hydrostatic pressure, and intermittent breath-holding subject aquatic athletes to unique physical and environmental stressors during swimming exercise. The relationship between exposure to aquatic exercise and both arterial stiffness and wave reflection properties is not well-understood. This study assessed central artery stiffness and wave reflection properties in elite pool-swimmers (SW), long-distance open-water swimmers (OW), and water polo players (WP) to examine the relationship between these variables and aquatic exercise. Methods: Athletes competing in SW, OW and WP events at the FINA World Championships were recruited. Carotid-femoral pulse wave velocity, and pulse wave analysis were used to quantify arterial stiffness, and central wave reflection properties. Results: Athletes undertook differing amounts of weekly swimming distance in training according to their discipline (SW: 40.2 ± 21.1 km, OW: 59.7 ± 28.4 km, WP: 11.4 ± 6.3 km; all p < 0.05). Pulse wave velocity (Males [SW: 6.0 ± 0.6 m/s, OW: 6.5 ± 0.8 m/s, WP: 6.7 ± 0.9 m/s], Females [SW: 5.4 ± 0.6 m/s, OW: 5.3 ± 0.5 m/s, WP: 5.2 ± 0.8 m/s; p = 0.4]) was similar across disciplines for females but was greater in male WP compared to male SW (p = 0.005). Augmentation index (Males [SW: - 3.4 ± 11%, OW: - 9.6 ± 6.4%, WP: 1.7 ± 10.9%], Females [SW: 3.5 ± 13.5%, OW: - 13.2 ± 10.7%, WP: - 2.8 ± 10.7%]) was lower in male OW compared to WP (p = 0.03), and higher in female SW compared to OW (p = 0.002). Augmentation index normalized to a heart rate of 75 bpm was inversely related to weekly swim distance in training (r = - 0.27, p = 0.004). Conclusions: This study provides evidence that the central vasculature of elite aquatic athletes differs by discipline, and this is associated with training load.